2015
DOI: 10.1016/j.asej.2015.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Effect of electrode material on electrical discharge machining of tool steel surface

Abstract: In this study the effect of electrode material was studied to avoid resulting residual stresses, the surface roughness and cracks resulted during Electrical Discharge Machining (EDM). Two types of EDM electrode materials were chosen, Dura graphite 11 and Poco graphite EDMC-3. Two grades of tool steels are chosen as test materials, DIN 1.2080 and DIN 1.2379. Different machining methods were chosen ''rough, medium, and soft'', it was found that the Dura graphite 11 exhibits more surface cracks upon DIN 1.2379 le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 12 publications
0
18
0
Order By: Relevance
“…Many studies with a focus on the surface integrity of tool steel materials during machining with different EDM variants were performed. For example, in an investigation [182], the effect of electrode material on resulting residual stresses, SR, and cracks in the surface of tool steel workpieces was studied. The research compared the machining performance while using Dura graphite 11 and Poco graphite.…”
Section: Effect Of Edm Process On the Surface Integritymentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies with a focus on the surface integrity of tool steel materials during machining with different EDM variants were performed. For example, in an investigation [182], the effect of electrode material on resulting residual stresses, SR, and cracks in the surface of tool steel workpieces was studied. The research compared the machining performance while using Dura graphite 11 and Poco graphite.…”
Section: Effect Of Edm Process On the Surface Integritymentioning
confidence: 99%
“…Changes in the chemical composition of re-solidified layers of the electrodes and the workpieces during the EDM of T215 Cr12 die steel were also been studied [91]. Many researches focused on the resulting residual stresses in the machined surface, such as Reference [182].…”
Section: Effect Of Edm Process On the Surface Integritymentioning
confidence: 99%
“…It was also noticed that lowering the pulse current results in the elimination of microcracks formation because of high thermal gradient below the melting zone. The residual stresses increase with soft machining due to higher pulse duration using Poco graphite electrode [82]. During the machining of steel using urea with deionized water, it was observed that machined surface is harder due to the presence of nitrogen concentration [83].…”
Section: Methods Of Improving Surface Qualitymentioning
confidence: 99%
“…Changes in the chemical composition of the re-solidified layers of the electrodes and workpieces were also studied during the T215Cr12 die steel EDM [ 3 ]. Several experiments centered on resulting residual stresses in the machined surface, for example, Reference [ 150 ].…”
Section: Relevant Studies On Pmedmmentioning
confidence: 99%